Live/love-streams: poetry and relating at the time of Covid-19 - Camille MANFREDI (E-REA)
This contribution considers how some of Scotland’s most popular poets have addressed and sometimes personally dealt with the inevitable consequences of the pandemic: beyond the disease itself, the cycle of denial-confusion-dismay, a renewed perception of the contingency of existence, fleeting moments of lightheartedness, and that which Michel Foucault termed “the practice of exile-enclosure” caused here by each successive lockdown. It examines the way poets rely on digital technology and the social media to foster online communities of readers, viewers, “friends” and “followers” and thus relate to the world by spreading contagion of another kind, be it emotional, aesthetic or otherwise, outside the conventional mechanisms of the commercial nexus.